Gewaltige Liebe Praktiken und Handlungsorientierungen junger Frauen in gewaltgeprägten Paarbeziehungen - Lohner, Eva Maria (Pädagogik, 2019)
How do young women experience violence in their first own relationships? What role do experiences of violence play in the family of origin and how do they shape one's own relationship conceptions? In the European context, the research discourse on violence in adolescent relationships is scarcely developed. Above all, however, the subject perspective is missing: the experiences that young and young women make in their first love relationships. Eva Maria Lohner makes clear the societal relevance of this perspective and shows that significant background points for socio-educational support and accompaniment can be deduced against her background.